A comparison of dementia assessment services for people with intellectual disabilities. Issue 3 (27th August 2021) - Gardner, Emile; Slater, Sean
Abstract : Purpose: This paper aims to describe three dementia assessment services for people with intellectual disabilities to provide professionals with insight into planning this type of service. Design/methodology/approach: Three services in England were contacted via email and telephone to collect data on their service provision. They were asked about the average age of individuals when receiving a baseline assessment, frequency of follow-up assessment, assessment instruments used and descriptive aspects of their services. Findings: All three services offered proactive dementia assessment services to people with Down's syndrome (DS), with one service providing systematic screening via the GP. None offered proactive screening to people with intellectual disabilities who did not have a diagnosis of DS. All offered reactive assessment to this population if they experienced a decline in function. Services differed in terms of age at which baseline assessments were offered, frequency of follow-up and instruments used. Originality/value: To the best of the authors' knowledge, this is the first paper to compare dementia assessment provision between different services in England.